1979
DOI: 10.1161/01.res.44.1.104
|View full text |Cite
|
Sign up to set email alerts
|

The effects of variations in conductivity and geometrical parameters on the electrocardiogram, using an eccentric spheres model.

Abstract: SUMMARY The effects of variations in the volume conductor properties of the torso on the electrocardiogram were studied by means of a theoretical eccentric spheres model. The model includes a blood cavity, cardiac muscle layer, pericardium, lung region, skeletal muscle layer, and subcutaneous fat. The source of the field is a double-layer spherical cap located within the myocardium. The following effects regarding the electrocardiogram (ECG) potentials were determined: (1) blood augments the potential, but les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 22 publications
1
34
1
2
Order By: Relevance
“…Mechanisms that underlie alterations of QRS voltage are changes in the generation and propagation of electrical currents in the myocardium, electrical conductivity of the intracavitary blood and the intervening tissues, the position of the heart, thickness of the ventricular wall and cardiac chamber size [23,24,25]. Among the clinically stable patients with hypothyroidism referred to our echocardiographic laboratory for cardiac assessment, low voltage was detected in 25%.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms that underlie alterations of QRS voltage are changes in the generation and propagation of electrical currents in the myocardium, electrical conductivity of the intracavitary blood and the intervening tissues, the position of the heart, thickness of the ventricular wall and cardiac chamber size [23,24,25]. Among the clinically stable patients with hypothyroidism referred to our echocardiographic laboratory for cardiac assessment, low voltage was detected in 25%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conductivity measurements require either acquiring electrical impedance tomography data or, e.g., somatosensory evoked responses, which is not always feasible. A second potential improvement to our results could be obtained by accounting for conductivity inhomogeneities and anisotropies within the layers of the head model (Peters and De Munck, 1991;Rudy et al, 1979), using e.g. finite-element methods (Haueisen et al, 1997).…”
Section: Limitations Of the Current Studymentioning
confidence: 99%
“…Using a theoretical eccentric spheres model, Rudy et al [9] showed that an 1 cm variation in the location of the heart produces a 24.2 percent variation in surface potential. This change in amplitude will also have a repercussion on the ECG spectrum.…”
Section: Effects Of Respiration On the Frontal Ecgmentioning
confidence: 99%